Efficacy and safety of perampanel oral loading in postanoxic super‐refractory status epilepticus: A pilot study. (29th August 2018) - Beretta, Simone; Padovano, Giada; Stabile, Andrea; Coppo, Anna; Bogliun, Graziella; Avalli, Leonello; Ferrarese, Carlo
Summary: Refractory nonconvulsive status epilepticus (NCSE) occurs in 10%‐30% of patients following resuscitation after cardiac arrest. Both the optimal treatment and prognosis of postanoxic status epilepticus remain uncertain. We analyzed acute electroencephalographic changes, neurological outcome at 3 months, and adverse effects in consecutive postanoxic patients with super‐refractory NCSE treated with add‐on oral loading of perampanel. Eight postanoxic patients with super‐refractory NCSE were treated with perampanel (dose range = 6‐12 mg). All patients had continuous electroencephalographic monitoring showing definite generalized NCSE and favorable multimodal prognostic indicators (presence of brainstem reflexes, presence of bilateral N20 responses, absence of periodic discharges/generalized epileptic periodic discharges). In six patients (75%), status epilepticus resolved within 72 hours after administration of perampanel, without changing the comedication. Neurological outcomes at 3 months were return to normal or minimal disability in four patients (50%). A mild cholestatic liver injury, which required no specific treatment, was observed in five patients (62.5%). Perampanel 6‐12 mg oral loading appeared to be an effective option in selected patients with postanoxic super‐refractory NCSE with good prognostic indicators. In this patient population, our safety data indicate a risk of cholestasis.